Hinduism and the Modem Age - Chackalackal, Werner (Journal of Dharma, 1976)
The first chapter "An Interpretative Survey Of The Growth Of The Hindu Religious Tradition" is a veritable panorama of Hinduism painted masterfully in broad strokes. In the second chapter quotations from a cross-section of western critics sets the background for apprais- ing the present trends of Hindu reform movements. Unfortunately, the western critics and admirers of Hinduism who have drawn the attention of Indian exponents of reform have mostly represented western secular views, which do not go to the roots of Hinduism as a religion and philosophy. The author senses clearly the task of religious reform to consist in "reappraising itself in relation to other religions of the world and in coping with the demand for adequate evidence in respect of beliefs and dogmas of every kind that the unprecedented successes of modern science and the prestige of scientific methods of investigation, have tended to foster." (p. 65).